Isolation and identification of infectious laryngotracheitis virus from outbreaks at Lipa City, Batangas, Philippines - Muharam Saepulloh; Hope G Rovira (Jurnal Ilmu Ternak dan Veteriner, 2003)
Infectious laryngotracheitis (ILT) is an acute, highly contagious respiratory disease of poultry characterized by respiratory disorder such as coughing with blood exudate from the trachea. The disease is caused by Herpesvirus of the family Herpesviridae and subfamily of Alphaherpesvirus. ILT is worldwide distribution and has been reported to be present in the Philippines since 1980. Since then, confirmation of subsequent outbreaks were not reported. Isolation was conducted from nine commercial layer chicken farms located at Lipa City, Batangas from May to July 2002. Tracheal and lung extracts were processed and inoculated into embryonated chicken eggs by chorio-allantoic membrane (CAM) inoculation. Five samples produced typical pock lesions in CAM after the second passage. Lesions observed were yellowish pocks with opaque edges, distributed throughout the CAM. A vaccine strain of the virus used as the positive control also produced similar pock lesions. Serological confirmation using the Agar Gel Immunodiffusion (AGID) test showed sharp precipitation lines reacting to a standard reference ILTV antisera (anti-NS175). All five isolates produced lines of precipitate identity among themselves and the positive control. This study confirms that the 2002 disease outbreak in the commercial layer chicken farms in Lipa City, Batangas was due to the ILTV.   Key words: Infectious laryngotracheitis virus, agar gel immunodiffusion, isolation, pocks lesion, identification, CAM